Assessment instruments of urban resilience - Saporiti, Giovanna; Echave, Cynthia; Scudo, Gianni; Rueda, Salvador (TeMA - Journal of Land Use, Mobility and Environment, 2012)
The objective of this work is to highlight the aspects related to the resilient capacity of a neoecosistema. Clarifying what does it means to speak about a resilient neoecosistema and which are the specific characters that make him capable of change and adaptation when facing an environmental, social or economic threat, it will be possible to understand the efficacy related to the model of urban development. From the individuation of perturbing factors of this capacity, it will be possible to generate a panel of the resilient capacity linked to three different ambits that represent the three characteristic elements of natural ecosystems: its physic structure, the persons and the interaction processes between them so we would be able to make explicit the specific characters of resilience distinguished from those of sustainability and urban quality.